Effects of Advertising on Consumer Behavior in Low Density Houses: The Case of Marlborough, Zimbabwe - Zinyemba, Alice Z; Manase, Irvine (International Journal of Business, Economics and Management, 2015)
This paper presents findings of a research that was carried out to establish the buying behavior of low density households in Zimbabwe and how they are influenced by the various forms of advertising. A questionnaire was administered to a sample of 75 respondents representing 75 households in Marlborough, Harare. The results of the study showed that 50% of the respondents strongly agreed that their decision to purchase a product was influenced by advertisements. They also indicated that they understood and preferred outdoor media more than television and print media which came second and third respectively in the order of preference. More than 75% of the respondents agreed that they bought advertised products more than those which are not advertised. The results also showed that consumers in Zimbabwe are slow in accepting and adopting the internet as a form of advertising. It can be concluded from this study that it definitely pays to advertise one’s products. It is also important that an advert should carry a strong message that is convincing to the consumers as indicated by 50% of the respondents. It can also be concluded that the Zimbabwean market has not yet fully embraced online advertising. The study recommends that outdoor media should be used more than any other forms of advertising in low density areas as it is the most preferred and most understood media choice. It is also recommended that since more women than men do the purchases for households in low density areas advertisements should target women more than men.